Beliefs and Habits Towards the Use of English Newspapers in Learning Autonomy - Shrestha, Bina (Research Nepal Journal of Development Studies, 2020)
The current era is an era of media and technology. Reading English newspaper is also a technological issue of language learning and teaching. Many studies have shown that autonomous learners are able to learn the language without being spoon-fed the information and assistance. Learners perform many activities inside the classroom and outside the classroom. The present article is the exploration of autonomic English learning strategies through newspaper reading. This study attempts to explore the students’ and teachers’ beliefs towards the use of English newspapers with reference to learning autonomy and it also aims to explore the habits of reading English newspapers. For this, both qualitative and quantitative data have been interpreted and analyzed. To examine the beliefs of students towards the use of English newspapers exit poll questionnaire survey was used. The key informant interview method also has been employed to explore beliefs of the teachers as well as the experiences regarding the reading newspapers and forming the habits of reading newspapers. Furthermore, the results suggest that students should use and read newspapers as an authentic and useful supplementary materials for improving their English language autonomously. Moreover, this study also asks the teachers to make students informed regarding the usefulness of newspapers for the part of learning English language.